Foaming and curing an aqueous epoxy foam using microwave - Erny Raudhoh, Mohd Shafie (Universiti Malaysia Perlis (UniMAP), 2019)
This study reports the effects of microwave energy, water content, and blowing agent concentration to the morphology, mechanical and thermal properties of aqueous epoxy foam based on polyamide-epoxy adduct. Samples of microwave energy were prepared at 160 to 320 watts of different microwave energy level and the samples of variation water content were formulated by using 25 to 200 phr of water content. Furthermore, the samples for variation of blowing agent concentration were produced using 0 to 4 phr of ammonium carbonate as blowing agent. Water was added as a green solvent and played as the void template. Mixing process of all ingredients was carried out based on their determined recipes by using an IKA overhead stirrer at speed 300 to 1200 rpm. Foaming and curing process were implemented using microwave oven. The foam samples were undergone 4 h post-cure at 70°C oven temperature. Morphology using Optical microscope (OM), Scanning electron microscope (SEM) showed that higher microwave energy and higher blowing agent concentration were better foaming and exist more cell interconnection. Increase of water content more than 100 phr, the aqueous mixture was changed from W/O system (water in epoxy resin) to W/O/W system (water in epoxy resin in water). This affects lower expansion and increase the gel time of sample W100 and W200. The foam characteristic and properties was found to be well reflecting the foams morphology. Theoretically, higher porosity caused lower compression stress but slight improved the thermal resistance at degradation temperature below 450oC due to lower heat transfer within the foam specimens. Compression set at room temperature exhibited an excellent recovery of 100%, which reduced to 95 – 68 % depending on foams formula if compressed at 70oC oven temperature. The study proves that the aqueous process is green, safe and no volatile organic compounds (VOCs). Besides of that, uses low concentration of blowing agent to produce epoxy foams with good performances.